Students' self-regulation conditions in traffic - Nurfarhanah Nurfarhanah; Rezki Hariko; Firman Firman; Zikry Latupasjana Ersya; Maya Mashita Rachmi (JRTI (Jurnal Riset Tindakan Indonesia), 2022)
Today traffic accidents that happen in domination by high school students, shows that traffic violations need important handling to be overcome. this research objects to analyze students' regulation conditions in traffic violations. This type of research is a descriptive study with a quantitative approach, using a data collection tool in the form of a self-regulation questionnaire in traffic. The subjects of this study were vocational high school students. The sample in this study was 65 vocational high school students. Subjects were taken by simple random sampling technique. This study uses data analysis techniques with descriptive analysis. The results of this study indicate that self-regulation consists of various aspects. Each aspect has a different percentage. The aspect of metacognition ability has a moderate percentage of 60.0%, the motivational aspect of self-regulation has the lowest percentage with 55.4%, while the behavioral aspect has a percentage of 66.2% in the medium category. The results of this study can be used as information for counseling teachers or counselors as a basis in efforts to provide assistance to students to improve adolescent self-regulation in traffic in order to prevent negative behavior, one of which is traffic violations that often occur in adolescents.